2021
DOI: 10.3390/pathogens10060750
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Prions in Brain Homogenates and CSF Samples Using a Second-Generation RT-QuIC Assay: A Useful Tool for Retrospective Analysis of Archived Samples

Abstract: The possibilities for diagnosing prion diseases have shifted significantly over the last 10 years. The RT-QuIC assay option has been added for neuropsychiatric symptoms, supporting biomarkers and final post-mortem confirmation. Samples of brain homogenates used for final diagnosis, archived for many years, provide the possibility for retrospective studies. We used a second-generation RT-QuIC assay to detect seeding activity in different types of sporadic and genetic prion diseases in archival brain homogenates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…We attempted to increase our sensitivity by testing fecal homogenates more concentrated than 10 −3 ; unfortunately, we found complete inhibition of the RT-QuIC assay when testing 10 −1 and 10 −2 fecal homogenates (data not shown). This finding is not unique to our study, and inhibition of the RT-QuIC assay has been reported previously when feces, brain, and other sample types have been tested ( 18 21 ). In the experiments described below, all lion fecal samples were initially tested using 10 −3 fecal homogenates.…”
Section: Resultssupporting
confidence: 79%
“…We attempted to increase our sensitivity by testing fecal homogenates more concentrated than 10 −3 ; unfortunately, we found complete inhibition of the RT-QuIC assay when testing 10 −1 and 10 −2 fecal homogenates (data not shown). This finding is not unique to our study, and inhibition of the RT-QuIC assay has been reported previously when feces, brain, and other sample types have been tested ( 18 21 ). In the experiments described below, all lion fecal samples were initially tested using 10 −3 fecal homogenates.…”
Section: Resultssupporting
confidence: 79%
“…CSF from P102L affected individuals has historically been tested by variations of PQ-CSF and IQ-CSF RT-QuIC, usually included as very small subsets within large surveys of national CJD surveillance cohorts, with low sensitivities(24-27, 47, 48) (Sano et al 2013(28) is an exception). P102L individuals in these papers were classified as GSS with little information provided about clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the IQ-CSF protocol contributed to significant development of the assay by showing retained high specificity, increased sensitivity, and a reduced assay time compared to the previous QuIC (PQ) protocol ( Table 3 ) ( Orrú et al, 2015a , 2020 ; Groveman et al, 2016 ; Park et al, 2016 ; Bongianni et al, 2017 ; Foutz et al, 2017 ; Franceschini et al, 2017 ; Rudge et al, 2018 ; Abu-Rumeileh et al, 2019 ; Fiorini et al, 2020 ; Rhoads et al, 2020 ; Vallabh et al, 2020 ; Xiao et al, 2020 ; Moško et al, 2021 ). In this regard, the IQ-CSF protocol showed a lower detection limit for seeding prions in a large patient cohort comprising the whole spectrum of human prions ( Franceschini et al, 2017 ).…”
Section: The Real Time Quaking-induced Conversion Assaymentioning
confidence: 99%